Lipopolysaccharide-Induced Cytokine Secretion from In Vitro Mouse Slow and Fast Limb Muscle. Issue 4 (17th April 2022) - Mattingly, Alex J.; Laitano, Orlando; Garcia, Christian K.; Robinson, Gerard P.; Clanton, Thomas L.
Abstract : ABSTRACT: Skeletal muscles play important roles in innate immunity. However, in vitro, their sensitivity to LPS is low. In other tissues, LPS sensing is facilitated by the presence of plasma, LPS binding protein (LBP), or soluble CD14 (sCD14). This study addressed whether these are critical for LPS sensitivity in skeletal muscle and whether LPS responsiveness is different between slow versus fast muscle. Soleus (SOL) or extensor digitorum longus (EDL) muscles from adult male C57bl/6 mice were mounted in 1 mL oxygenated baths containing: buffer only; buffer+1% mouse plasma; buffer+1 μg/mL LBP; or buffer+1% plasma from sCD14 -/- mice. In each condition, muscles were exposed to LPS from 0 μg/mL to 1.0 μg/mL. Bath samples were collected at 0, 1, and 2 h, and analyzed using cytokine multiplex arrays. In both SOL and EDL the predominant responding cytokines/chemokines were KC(CXCL1), IL-6, and MCP-1(CCL2) and their average responses were amplified by ∼10-fold in the presence of 1% plasma. Overall, SOL and EDL exhibited similar secretory responses in the presence of 1% plasma, with a lower limit of sensitivity to LPS of 0.01 μg/mL. LBP supplementation did not augment secretion; however, 1% plasma from CD14 -/- mice suppressed cytokine/chemokine secretion from EDL muscle. In conclusion, intact slow and fast mouse muscles have similar cytokine/chemokine responses to LPS but depend on the presence of low levels of plasma constituents. Though sCD14 plays some role in EDL muscle, neither sCD14 nor LBP can fully account for the strong effects of plasma on LPS sensitivity.